Analisis Inovasi Produk Layanan (E-Banking) Terhadap Peningkatan Fee Base Income Pada Pt. Bank NTB Syariah - Ansyary, Muhammad Isa; Dharmayanda, Hardian Reza; Dharmawansyah, Dedy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Along with the times, science and technology have developed so rapidly, one of which is digital technology, where digital technology has entered all lines of human life, even this digital technology is able to influence human life and habits where the presence of digital technology provides convenience to the public to complete their work quickly, easily and efficiently and effectively by using electronic features. The development of this technology is also used by the banking world in addition to improving services but also to increase profitability by making innovations to E-Banking products. This study was conducted to determine and analyze the effect of product service innovation (E-Banking) on the increase in Fee Base Income at PT. Bank NTB Syariah. Data analysis was carried out by quantitative analysis using the Structural Equation Modeling method. The results showed that the development and innovation carried out on the features of the E-Banking service product of PT. Bank NTB Syariah has an effect on increasing the number of transactions so that it has an effect on increasing the income of each E-Banking service product. This increase in service product income (E-Banking) has an effect on increasing the Fee Base Income of PT. Bank NTB Syariah. The results also show that Mobile Banking Income has a significant effect with a P-Value value of 0.002 and a path coefficient value of 0.434, while ATM income has a positive but not significant effect with a P-Value value of 0.122 and a path coefficient value of 0.182. And EDC income has a significant but negative effect with a path coefficient value of -0.253 and a P-Value value of 0.049.